Uso de geotecnologias na identificação e mapeamento dos atores do desmatamento na frente pioneira de São Félix do Xingu - PA - MACEDO, Magno Roberto Alves (Universidade Federal do Pará, 2021)
The fronts in the Brazilian Amazon are mainly responsible for altering the regional landscape, and are characterized by the advance of the forest at breakneck speed and proportion. As a result of this advance, there is the construction of new infrastructure in poor areas with high rates of deforestation, with social problems arising from lack of territorial planning of these areas. This work aims at identifying and monitoring the behavior of actors involved in the deforestation of the pioneer front in Sao Felix do Xingu / PA, in the period 2001 to 2008, through the interaction between the forms identified in remote sensing image data and social, economic, productive, from studies done in the region. The results show that the method presented has differentiated its efficiency, and satisfactory answers in the most advanced front of the border ("front face" and "middle front), and decreased efficiency in the areas of higher occupation of the front (rear front). However the responses from responding quickly to possible changes in the pioneer front, supporting the development of rapid diagnostics of these regions and their use in public policy planning.